Monetary policy transmission and bank interest rates in Nigeria - Victor E. Eleam; Chinyelu G. Ekwom; Chibueze C. Ariolu; Chukwubuzo J. Umebali; Adewale T. Balogun (CBN Journal of Applied Statistics, 2021)
The paper examines the adjustment of retail and money market interest rates to changes in discount corridor of the monetary policy in Nigeria. A vector error correction model was adopted for this study, using monthly data from 2007:06 to 2019:12. We further accounted for structural breaks in the dataset to improve its policy reliability. The adjustment parameters were found to be significant but with slow speed of adjustment. This finding provides evidence of the weakness of the dis- count corridor in monetary policy transmission in Nigeria. Furthermore, the results showed no asymmetric adjustment of retail rates to long run equilibria. Lastly, the study found that the deposit rates respond inversely to changes in the standing lending facility. The results imply that the transmission of policy signals through the standing facility rates is not strong, and that raising the standing lending facility will not induce a rise in banks' deposit rates.
Keywords: E43; E52; E58; 330; Discount window operations; monetary policy; standing facilities